Biofiltration of hexane, acetone and dimethyl sulphide using wood, compost and silicone foam. Issue 8 (6th March 2018) - Bruneel, Joren; Walgraeve, Christophe; Mukurarinda, Juvenal; Boon, Nico; Van Langenhove, Herman
Abstract: BACKGROUND: Biofiltration is a technique to remove volatile organic compounds (VOCs) from waste gas streams. It can be regarded as a sustainable treatment technology with low operational costs and good performance. The treatment of hydrophobic compounds is however difficult, due to the low mass transfer towards the water phase on top of the biofilm present on the packing material. To overcome this mass transfer limitation, a hydrophobic silicone foam was added to a conventional biofilter containing compost and wood dowels. RESULTS: The biofilter was operated for 180 days to treat acetone, hexane and dimethyl sulphide at an empty bed residence time of 57 s with inlet load varying up to 4.5 g m 3 h ‐1 . The highest removal efficiency of acetone, dimethyl sulphide and hexane was, respectively, 99%, 80% and 50%. The affinity of the target compounds towards the packing material was quantified in terms of the packing material‐to‐air partitioning coefficient, which was measured using a SIFT‐MS based breakthrough approach. These experiments revealed that hexane has a 20 to 100 times higher affinity for silicone foam than compost and wood. Microbial community analysis was performed on the different substituents of the packing material at the inlet and outlet. No significant differences in relative abundance were observed between the types of packing materials. Comparison with literature revealed the presence of bacterial strains that were not yet reported in biofilter studies. CONCLUSION: Silicone foam in a biofiltration set‐up showed good performances against the degradation of the target VOCs and mass transfer to the packing material can be increased. © 2018 Society of Chemical Industry